Pollination systems in a remnant of Atlantic forest (Research, Society and Development, 2020)
Pollination systems in a remnant of Atlantic forest – Plant-animal interaction processes, such as pollination, which is the transference of pollen from the anthers to the stigma through biotic and/or abiotic vectors, are important to the comprehension of communities’ dynamics. This study describes the pollination systems found at an area of Atlantic forest in the Brazilian State of Paraíba and characterizes the floral morphology of the species therein. Guaribas’ Biological Reserve is located at Mamanguape’s municipality – Paraíba. The floral material was collected at pre-existent trails and analyzed in laboratory. A total of 111 species belonging to 96 genera and 46 families was studied. The most common traits were: light-colored flowers, with no smell, small size, tubular-type corolla, actinomorphic symmetry and hermaphroditism. Five main pollination syndromes were found, in which species were self-distributed as follows: melittophily (82%), ornithophily (8%), psicophily and sphingophilous (4.5%), and chiropterophily (1%). In natural ecosystems plant-animal interactions are important to environmental dynamics and structure. The occurrence of melittophilous species has been describe as a prevalent attribute in the Atlantic forest, also found in this study.